SEJARAH BERDIRINYA SD NEGERI 01 SIAK SEJAK 1915 HINGGA KEMERDEKAAN RI 1945 - Habib Sugiarto Habib Sugiarto; Ridwan Melay Ridwan Melay; Kamaruddin Kamaruddin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Education is one way for people to reach a level of progress, as a means to free itself from underdevelopment, and various social shackles that impede the achievement of the common welfare, reciprocation of a nation depends on whether or not the quality of education obtained.Dutch colonial period with regard to education is a dark history. Occupiers make education as a tool to reap profits through cheap labor. Schools were also made at low cost, in order not to burden the government coffers.Educational facilities of high quality is always maintained during the colonial period that keep children Netherlands always get a better education of the children of Indonesia because the Dutch government did not want any indigenous children who will be able to compete with the Dutch Later onset of the notion that profits acquired by the Dutch over the colonies should be paid back. The events that can be viewed as an expression of a new idea that came to be known as the Ethical Policy. Finally built a school for indigenous people, equivalent to the school for the Europeans. This study aimed to determine the background of the establishment of the State Elementary School 01 Siak, know the development of the State Elementary School 01 Siak year 1915-1945, to know what the role of the State Elementary School 01 for the community Siak.Results of research in general researchers can say that the establishment of SD Negeri 01 Siak due to the pressure exerted by the Dutch against the kingdom Siak which the school stood in 1915 during the 12th Sultan Kingdom of SiakKeywords: History , Netherlands School, Siak Sri Indrapura